Economic Crisis and Muslims’ Decisions to Immigrate to France Diagnosis and Forecast (Economic and Political Thought, 2012)
The article aims at answering the question whether the economic crisis(of the 1970s and the first decade of the 21st century) has impact on theMuslims’ decisions to immigrate. In order to illustrate this issue, I assumedit was necessary to discuss some historical aspects of immigration to France,which in the 1940s and 50s was mainly a goal for the citizens of Italy, Spainand Portugal. The influx of Muslims to France dates back to 1962, whenAlgeria gained independence, and has continued until now. As demographers,sociologists and political science experts highlight, the economic crisis does notinfluence the immigration decisions of Muslims from the poor countries of theNorth Africa and the Middle East. The main factor stimulating immigrationof Muslims is the economic development level in their countries of origin.It is true that the number of Muslim immigrants is slightly decreasing but itis due to the restrictive immigration policy adopted by the host countries, i.e.the increase in the deportation quotas or the so-called selective immigration.The economic crisis made the host countries’ societies show their antiimmigrationattitudes. The anti-Muslim attitude of the most importantFrench politicians is also important. The example can be the Presidentof the National Front – Marine Le Pen, who states “the economic crisis(including the one in France) results from supporting Muslims”, and theformer President of France – Nicolas Sarkozy – famous for his ‘iron hand rulepolicy’ and controversial opinions about Muslims.The article ends with a hypothesis that the immigration policy of Franceis mainly influenced by such factors as cultural identity maintenance, andintegration and/or security policy rather than a strictly economic factor.